Peculiarities of legal regulation of compulsory termination of land ownership in the conditions of the legal regime of martial law in Ukraine - Nastina, Olga (ScienceRise: Juridical Science, 2022)
The purpose of the study is to analyze the principles of land law regulation and the legal framework for the forced termination of private ownership of land and the acquisition of state ownership of land under martial law. The following scientific tasks are solved in the article: the content of some grounds for termination of private ownership of land plots, which are the grounds for state acquisition of land ownership under the legal regime of martial law; the procedure of compulsory alienation and seizure of land plots under martial law is analyzed, gaps in the current legislation are identified and ways of settling legal conflicts are proposed. The elaboration of the topic is based on the provisions of the general theory of land and civil law, where, taking into account the latest advances in science, conceptual recommendations are provided for building a legal structure of forced termination of land ownership. The research was conducted on the basis of an analysis of the provisions of Ukrainian civil and land legislation, measures of forced alienation and seizure of land. The article provides coverage of current issues and legislative features of the termination of private ownership of land and the acquisition of state rights of landowners under martial law. The existence of the procedure of forced alienation of property, the procedure of forced seizure of property in favor of the state, different in form, content and mechanism in the legal regulation, is explained. The forcible termination of the right of private ownership of land under martial law entails the acquisition by the state of the rights of the owner. Compulsory alienation of land must follow the advance payment of alienation; the procedure for withdrawing land for the needs of the state may provide for the following reimbursement. Proposed ways to resolve legal conflicts by systematizing the grounds for state acquisition of property rights in martial law and filling gaps in legislation, by developing a separate mechanism that regulates the procedure of forced expropriation of land in martial law, decisions to determine the list of land, for which forced expropriation or seizure of land may be applied.